2022
DOI: 10.1177/11206721221146674
|View full text |Cite
|
Sign up to set email alerts
|

Swept-source optical coherence tomography angiography automatic analysis of microvascular changes secondary to systemic hypertension

Abstract: Introduction The aim of our study is to report swept-source optical coherence tomography angiography (SS-OCTA) quantitative parameters of retinal and choroidal microvasculature in patients with systemic hypertension (HTN) using a built-in software of SS-OCTA. Methods We performed a retrospective study. This study enrolled 93 eyes of 51 subjects with HTN and 71 eyes of 38 healthy subjects. OCTA quantitative parameters (vessel density (VD) and foveal avascular zone (FAZ) area of superficial capillary plexus (SCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Parafoveal VD in the choriocapillaris, DCP, and total capillary plexus was also found to be decreased in hypertensive patients versus those of controls [22]. Conversely, no significant difference was found in the SCP and middle capillary plexus between hypertensive and control patients [22]. Similar results were obtained in another study in which there was a significant decrease in VD between hypertensive and control eyes in the DRL, but no significant difference in the VD of the SRL [23].…”
Section: Systemic Arterial Hypertensionsupporting
confidence: 82%
See 2 more Smart Citations
“…Parafoveal VD in the choriocapillaris, DCP, and total capillary plexus was also found to be decreased in hypertensive patients versus those of controls [22]. Conversely, no significant difference was found in the SCP and middle capillary plexus between hypertensive and control patients [22]. Similar results were obtained in another study in which there was a significant decrease in VD between hypertensive and control eyes in the DRL, but no significant difference in the VD of the SRL [23].…”
Section: Systemic Arterial Hypertensionsupporting
confidence: 82%
“…Bridging this concept, Donati et al [21] showed a significant reduction in the VD of the DRL and an enlargement of the deep FAZ area in hypertensive patients, thus suggesting the presence of an early modification of the microvascular network at the level of the deep retinal plexus [21]. Parafoveal VD in the choriocapillaris, DCP, and total capillary plexus was also found to be decreased in hypertensive patients versus those of controls [22]. Conversely, no significant difference was found in the SCP and middle capillary plexus between hypertensive and control patients [22].…”
Section: Systemic Arterial Hypertensionmentioning
confidence: 94%
See 1 more Smart Citation